STATUS MUTU AIR SUNGAI SIRAU SUB DAS SIRAU DI DAS BARITO KABUPATEN BARITO TIMUR PROVINSI KALIMANTAN TENGAH - Ringkas Lelunuto; Muhammad Ruslan; Kissinger Kissinger; Fatmawati Fatmawati (Universitas Lambung Mangkurat, 2019)
Sirau River is one of the rivers in the Barito Timur Regency which flows through the Dusun Timur District. Sirau River water is used as raw material for regional water companies (PDAM) and is used by communities around the river to meet the needs of other daily life such as MCK and other uses and is also used as a landfill, domestic wastewater and waste water mining and plantation activities both directly and indirectly. This study aims to analyze the status of pollution of the Sirau river through the approach of the pollution index value, assess the quality of the Sirau River water and identify the source of pollutants entering the Sirau River. The results showed that in general the water quality of the Sirau River for pH, COD, BOD, Fe, and Mn parameters exceeds the water quality standard namely Government Regulation No. 82 of 2001 class II concerning Water Quality Management and Water Pollution Control, the main source of pollutants comes from residential domestic waste, coal mining activities and dry leaves that fall into river streams. Sirau river water quality from upstream to downstream based on river water quality analysis using the pollution index method shows that water quality has decreased where the river conditions are generally mildly polluted. The quality of lightly polluted Sirau river water cannot be utilized in accordance with the designation of class II water based on Government Regulation No. 82 of 2001 concerning Management of Water Quality and Water Pollution Control.